Splenectomy in conditions of the pancreas - Mérola, Lorenzo (Cirugía del Uruguay, 1973)
Following clínica! observation of a patient the author presents the hypothesis that splenectomy favours an increase of splenic artery flow towards pancreas. and is thus beneficia! to it.